Evaluation of the acerola juice concentrated by reverse osmosis - Gomes,Eliane Rodrigues dos Santos (2005)
The aim of this study was to obtain the acerola juice using separation processes with membranes. The acerola pulp was initially defrosted and treated with 100 ppm of Citrozym Ultra L enzyme at 45ºC for one hour, then ultrafiltrated at 3 bar at 45ºC using 0.1 µm ceramic membrane, and concentrated by reverse osmosis using a spiral membrane of a compound film. The pressures on the reverse osmosis were 20, 30, and 40 bar at environmental temperature, thus, resulting a juice with 9.76, 14.56, and 17.36 ºBrix, respectively. The physicochemical characteristics of the juice were preserved and, studies on evaluation of the public acceptability, showed that 75% of the consumers liked the juice.